PEMBINAAN INDUSTRI KREATIF PADA JIWA KEWIRAUSAHAAN MASYARAKAT - Zefri Azharman; Elva Susanti (PUAN INDONESIA, 2020)
Human resources (HR) are important in the industrial world, without human resources, natural resources will not develop into high-value finished materials. Knowledge towards the creative industry is not yet available if it has not been given to the community, therefore the community needs to be fostered in the field of creative industries in terms of changing raw materials into finished materials, in terms of changing unused materials into finished goods, in terms of how to find the right opportunities in the field small industries and so on. With the guidance of the community, it is expected that the community will be able to be creative and understand the importance of the creative industry in the field of entrepreneurship. The creative industry implemented is the manufacture of healthy salted eggs without harmful chemical preservatives. Utilizing rubbing ash and salt can increase the resistance of duck / duck eggs and provide a high selling price. The activities carried out are needed by the PKK community who routinely carry out creative activities including the creative industries to increase entrepreneurship.